Whole-Body EMS Superimposed Walking and Nordic Walking on a Treadmill—Determination of Exercise Intensity to Conventional Exercise - Verch, Ronald; Stoll, Josephine; Hadzic, Miralem; Quarmby, Andrew; Völler, Heinz (Frontiers in Physiology, 2021)
Electrical muscle stimulation (EMS) is an increasingly popular training method, which has become the focus of research in recent years. New EMS-devices offer a wide range of mobile applications for whole body EMS training, e.g. the intensification of dynamic low-intensity endurance exercises through whole body electrical muscle stimulation (WB-EMS). The aim of the present study was to determine the differences in exercise intensity between WB-EMS superimposed and conventional walking, and conventional and WB-EMS-superimposed Nordic-walking during a treadmill test. Eleven participants (52.0 ± years; 85.9 ± 7.4 kg, 182 ± 6 cm, BMI 25.9 ± 2.2 kg/m2) performed a ten-minute treadmill test at a given velocity (6.5 km/h) in four different test situations, walking (W) and Nordic-walking (NW) in both conventional and WB-EMS superimposed. Oxygen uptake in absolute (VO2) and relative to body weight (rel.VO2), lactate and rate of perceived exertion (RPE) were measured before and after the test. WB-EMS-intensity was adjusted individually according to participant’s feedback. Descriptive statistics were given in mean ± standard deviation (SD). For statistical analyses, one-factorial ANOVA for repeated measures and two-factorial-ANOVA (factors: EMS, W/NW, EMS*W/NW) were performed (α=0.05). Significant effects were found for factors EMS and W/NW for the outcome variables VO2 (EMS: p=0.006, r=0.736; W/NW: p<0.001, r=0.870), relative VO2 (EMS: p<0.001, r=0.850; W/NW: p<0.001, r=0.937) and lactate (EMS: p=0.003, r=0.771; w/NW: p=0.003, r=0.764) whereby both factors produced higher results. However, the difference in VO2 and relative VO2 are within the range of biological variability of ±12%. The factor combination EMS*W/NW is statistically non-significant for all three variables. WB-EMS resulted in higher RPE values (p=0.035, r=0.613), RPE differences for W/NW were not significant as well as factor combination. Our results indicate that WB-EMS influences parameters of exercise intensity. The impact on exercise intensity and the clinical relevance of WB-EMS superimposed walking exercise is questionable because of the marginal differences in outcome variables.